Synthesis, characterization and thermal degradation of poly[2-(3-p-bromophenyl-3-methylcyclobutyl)-2-hydroxyethylmethacrylate] - Demirelli, K; Coskun, M (John Wiley & Sons Ltd, 1999)
In this work, 2-(3-p-bromophenyl-3-methylcyclobutyl)-2-(BPHEMA) [monomer] was synthesized by the addition of methacrylic acid to 1-epoxyethyl-3-bromophenyl-3-methyl cyclobutane. The monomer and poly(BPHEMA) were characterized by FT-IR and [H-1] and [C-13]NMR. Average molecular weight, glass transition temperature, solubility parameter, and density of the polymer were also determined. Thermal degradation of poly[BPHEMA] was studied by thermogravimetry (TG), FT-IR. Programmed heating was carried out at 10 degrees C min(-1) from room temperature to 500 degrees C. The partially degraded polymer was examined by FT-IR spectroscopy. The degradation products were identified by using FT-IR, [H-1] and [C-13]NMR and GC-MS techniques. Depolymerization is the main reaction in thermal degradation of the polymer up to about 300 degrees C. Percentage of the monomer in CRF (Cold Ring Fraction) was estimated at 33% in the peak area of the GC curve. Intramolecular cyclization and cyclic anhydride type structures were observed at temperatures above 300 degrees C. The liquid products of the degradation, formation of anhydride ring structures and mechanism of degradation are discussed. (C) 1999 Society of Chemical Industry.
Keywords: synthesis; thermal degradation; 2-hydroxyethylmethacrylate